Influence of surface treatment on the strength of adhesive joints - Doluk, Elzbieta; Rudawska, Anna; Stancekova, Dana; Mrazik, Jozef (Manufacturing Technology Journal, 2021)
The article compared the strength results of single-lap adhesive joints made of galvanized steel sheet. The strength of adhesive joints was determined for two methods of surface treatment - using a degreaser (method B) and with-out a degreaser (method A). The samples were joined using a two-component epoxy adhesive based on Bisphenol A. The strength tests were carried out on a Zwick/Roell Z150 testing machine. The analysis of the surface roughness parameters of the samples for the method A was performed. The highest shear strength value (8.82 MPa) was ob-tained by method B and using P120 abrasive paper. The lowest shear strength value (4.08 MPa) was received using method A and P600 abrasive paper. The maximum values of measured surface roughness parameters were rec-orded for samples prepared with abrasive papers with granulations, respectively: P120, P220 and P180. The low-est values of Ra, Rz and Rt parameters gained using P600 abrasive paper.
Keywords: adhesive joints; shear strength; adhesive composition; degreasing; roughening